The Afropolitan flâneur: literary representations of the city and contemporary urban identities in selected African and transnational texts - Leff, Carol Willa (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2019)
When an individual walks the urban landscape there is a unique symbiosis between self and city. It is through walking the cityscape and observing the crowd and the surrounding environment that the archetypal literary figure of the European flâneur acts as a mirror of a particular time and space. But how might such a flâneur walk and observe the city in contemporary African and transnational literary texts? I argue that there is a literary re-imagining and repurposing of the flâneur figure which has hitherto not been acknowledged and explored: an Afropolitan flâneur. 'Afropolitan' is a term popularised by Taiye Selasi in a 2005 essay to refer to a 'scattered tribe' of 'Africans of the world' (n. pag.). In this dissertation, the entanglement of the Afropolitan subject and the European flâneur brings together past and present, Africa and the West. I first provide a historical and theoretical framework to illustrate how the flâneur figure 'migrated' from Europe to Africa, and how this figure is to be understood as a literary construct, in relation to current considerations of Afropolitanism. I go on to discuss a wide range of texts that engage with Afropolitan flâneurs who traverse cities in Africa (such as Johannesburg, Cape Town and Lagos), or global north cities (New York, Paris and London). While some of the Afropolitan flâneurs depicted in these texts are migrants or homeless individuals who struggle to adapt easily to a new environment, others, despite being more privileged, also sometimes experience uncomfortable assimilation in their new or strange city space. There are also those who seem to feel equally at home wherever they find themselves. As these Afropolitan flâneurs walk their way through the urban landscape in the texts under examination, they reflect different ways of being in the city. By problematising the binaries of local/global, national/transnational, black/white, slum/paradise, this dissertation seeks to address issues of belonging or not belonging and gestures towards new ways of understanding what it means to be an African in the world.
Keywords: City and town life in literature; African literature (English) -- History and criticism; Flaneurs in literature